Fruiting Season, Flowering and Peel Characteristics of Leucaena spp. Analytical Study (B): Analytical Studies of Leucaena spp. - Hassan Al-Bugg, Younis Saeed (Biological Sciences - PJSIR, 2021)
During the flowering seasons the species varied greatly and the seasons were seldom repeated (August-October) with only three species and two species (April-June), which means that they continued throughout the months of the year. Three colours of the flower were observed in total with gradient within these three colours distributed to the studied species. In terms of the colour of the peel, two colours were distinguished only in favour of the brown-gray colour, while the forms of cracks on the outer peel surface were divided into three forms. On the other hand, each type was independent when examining the colour of the inner peel. The shape of the cross section of the branch exceeded 81.8% for the circular shape on the angular shape, while two types of branch thickness were recorded and exactly the same for texture. It was possible to observe two forms of branching of the flower-bearing branches, which were very similar to those of the two forms (non-branching and branching) with a large difference between the two forms of the flower’s apex, at a rate of 20 times the round shape and 90.9% of the shape of the flower. Two flowers shoots growing types were observed named (Auxotelic and an Anauxotelic). Three main colours, white, yellow and pink were distinguished and the flower head diameter varied widely between (6.5-30 mm). Flowers season seems to be in all of the year. Outer peel thickness also varied from thick to thin to intermediate. Three forms of peel fissures were found and 54.5% to mid-brown colour. Inner peel colour can be a good item to be a key of classification of this tree. Correlation coefficient between peel thickness and outer peel colour was 0.935.